Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445125
|View full text |Cite
|
Sign up to set email alerts
|

Producing Liveness

Abstract: The global pandemic has driven musicians online. We report an ethnographic account of how two traditional folk clubs with little previous interest in digital platforms transitioned to online experiences. They followed very different approaches: one adapted their existing singaround format to video conferencing while the other evolved a weekly community-produced, pre-recorded show that could be watched together. However, despite their successes, participants ultimately remained unable to 'sing in chorus' due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Live streaming has existed for over two decades as a form of real-time entertainment, which provides equal opportunities for everyone to present themselves online [42]. Since the outbreak of COVID-19 in 2020, some offline on-site activities, such as folk clubs [3] and fitness classes [12], have also been increasingly transformed to online via live streaming. Live streaming platforms (e.g., Twitch) have attracted countless streamers so anyone can find suitable channels and live content they want [48].…”
Section: Video Game Live Streaming and Beyondmentioning
confidence: 99%
“…Live streaming has existed for over two decades as a form of real-time entertainment, which provides equal opportunities for everyone to present themselves online [42]. Since the outbreak of COVID-19 in 2020, some offline on-site activities, such as folk clubs [3] and fitness classes [12], have also been increasingly transformed to online via live streaming. Live streaming platforms (e.g., Twitch) have attracted countless streamers so anyone can find suitable channels and live content they want [48].…”
Section: Video Game Live Streaming and Beyondmentioning
confidence: 99%
“…A recent study of how traditional folk clubs moved their activities on-line during the global pandemic revealed how participants appropriated existing social platforms including Zoom and Facebook to innovate a new format that mixed live and pre-recorded content. The study reported how traditional musicians adopted new digital practices such as the use of visual backdrops and group edited videos, but also how their traditional practices were in turn influenced by their choice of technologies, for example through a perceived pressure to keep producing new material rather than repeating previous tunes and songs as would normally happen when face-to-face [7].…”
Section: Online Performancesmentioning
confidence: 99%
“…( Afonso et al, 2020 ; Gaggi et al, 2020 ; Kelly et al, 2021 )) and leisure behavior (cf. ( Benford et al, 2021 ; Niu et al, 2021 ; Yeung, 2020 )) have been explored in recent studies from a human-computer interaction (HCI) perspective, food practices, and in particular the media and technology used during those practices in pandemic times, are rarely examined (cf. ( Ceccaldi et al, 2020 )).…”
Section: Introductionmentioning
confidence: 99%